Technical design and production of special effects in musical theatre performances - Hashim, Hafshizan; Zulkepeli, Mohd Kamil; Abd Rahman, Khairul Aidil Azlin; Siu, K.W.M. (e-IPH, 2023)
In contrast to the other theatre form, which requires a more predominately dominant combination of acting, singing, music, and choreography, a musical theatre performance is a sophisticated piece of art. Similarly, paying greater attention to the technical special effects design is essential, especially throughout its production process. In order to clarify their requirements and design objectives, this study explores the features of the technical special effects used in the selected case studies. The result shows how well the entire musical theatre production includes customisation requirements and solutions in developing the technical design of special effects production.